2020
DOI: 10.1111/eci.13408
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endoclip papilloplasty preserves sphincter of oddi function

Abstract: Background Endoscopic sphincterotomy (EST) can destroy sphincter of Oddi (SO) structure and function. The purpose of this study was to assess the feasibility of endoscopic endoclip papilloplasty (EEPP) in restoring SO function after EST. Methods Seven 26‐week‐old domestic pigs were divided into control and EEPP groups. Necropsy and haematoxylin‐eosin staining plus anti‐α‐smooth muscle actin (α‐SMA) staining of papilla and sphincter of Oddi manometry (SOM) were conducted in animals at three independent time poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, organ-preserving and function-preserving surgical techniques are quickly emerging. Examples include pylorus-preserving radical gastrectomy [ 19 ], duodenum-preserving pancreatectomy [ 20 ], and duodenal papillary sphincteroplasty with preservation of the sphincter of Oddi [ 21 ]. We utilized laparoscopic techniques for skeletonizing the ICA, and blood perfusion for ileocecal-colic anastomosis was secured by selective vessel preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, organ-preserving and function-preserving surgical techniques are quickly emerging. Examples include pylorus-preserving radical gastrectomy [ 19 ], duodenum-preserving pancreatectomy [ 20 ], and duodenal papillary sphincteroplasty with preservation of the sphincter of Oddi [ 21 ]. We utilized laparoscopic techniques for skeletonizing the ICA, and blood perfusion for ileocecal-colic anastomosis was secured by selective vessel preservation.…”
Section: Discussionmentioning
confidence: 99%
“…[138] Additionally, circ_0 0 08078 can inhibit the tube formation ability of esophagus cancer via interfering the ELOVL4mediated lipid metabolism. [118] Lymphangiogenesis, like angiogenesis, involves the formation of new vessels, but in this case, it is new lymphatic vessels forming from pre-existing ones. This process is considered an important step in lymph node metastasis in cancer.…”
Section: The Lipid Metabolic Related Lncrnas-circrnas In Angiogenesis...mentioning
confidence: 99%
“…For the elongation of de novo fatty acids, circ_0 0 08078 was identified to be downregulated in esophagus cancer (EC), which promoted ELOVL4 expression via miR‐191‐5p, and regulated the proliferation, tube formation, migration and invasion of EC. [ 118 ] For the desaturation of de novo fatty acids, these lipid‐metabolic related lncRNAs and circRNAs can involve the SCD‐mediated desaturation of de novo fatty acids. For instance, a novel linc00174 has been identified to modulate the SCD5‐meditated lipid production by absorbing miR‐145‐5p in thymic epithelial tumors (TETs).…”
Section: Lncrnas‐circrnas Regulate the Rewiring Of Lipid Metabolism I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng and Dong [ 32 ] suggested that patients with iatrogenic injury of the sphincter of Oddi should be treated with transduodenal sphincteroplasty to restore the structural integrity of the sphincter and reduce biliopancreatic duct complications secondary to loss of function. Recently, Wang et al [ 33 ] reported that endoscopic endoclip papilloplasty (EEPP) had accelerated and improved the papillary healing after EST and preserved the physiological function of the sphincter of Oddi. The importance of this report is that EEPP may be a safe and potentially beneficial procedure in reducing post-EST complications.…”
Section: Urgent Standardization Of Minimally Invasive Surgery In Geri...mentioning
confidence: 99%